Effect of charge accumulated at oil–paper interface on parameters considered for power transformer insulation diagnosis. Issue 3 (1st May 2018) - Mishra, Deepak; Haque, Nasirul; Baral, Arijit; Chakravorti, Sivaji
Abstract : Polarisation and depolarisation current (PDC) measurement and analysis is one of the popular tools for effective diagnosis of power transformer insulation. Normally, it is assumed that polarisation current is the combination of the current due to dipole movement and conduction current. Similarly, the depolarisation current is only due to the relaxation of dipoles. However, it is found that after eliminating the effect of dc conduction from polarisation current the resulting current is not similar to that of measured depolarisation current. This shows some non‐linearity is present in the system. This non‐linearity occurs due to movement of trapped charge that resides in the interfacial region of oil–paper insulation. This study shows the effect of de‐trapping charge on various performance parameters that are used for insulation diagnosis like paper moisture and dielectric dissipation factor (tan δ ).